REL-1017 (Esmethadone), A Novel NMDAR Blocker for the Treatment of MDD is Not Neurotoxic in Sprague-Dawley Rats - Bifari, Francesco; Pappagallo, Marco; Bleavins, Michael; Traversa, Sergio; Folli, Franco; Manfredi, Paolo L. (Frontiers in Pharmacology, 2022)
REL-1017 (esmethadone; dextromethadone; (S)-methadone) is the opioid-inactive dextro-isomer of the racemic mixture, (R, S)-methadone. REL-1017 acts as a low affinity, low potency N-methyl-D-aspartate receptor (NMDAR) channel blocker with rapid, robust, and sustained therapeutic effects in patients with major depressive disorder (MDD). Systemic administration of NMDAR blockers may cause transient and reversible pathomorphological alterations in brain cortical neurons characterized by cytoplasmic vacuolization, which are called Olney’s lesions, and may also lead to irreversible neuronal necrosis. We determined whether REL-1017 administration via oral gavage for 1–4 days to Sprague-Dawley rats could produce Olney’s lesions and cortical neuronal death and microgliosis as compared with MK-801, a known neurotoxic potent NMDAR blocker. As previously reported, MK-801 produced Olney’s lesions, neuronal necrosis and cortical microgliosis, and impaired behavior and activity. In contrast, administration of REL-1017 at low (20–31.25 mg/kg in females and males), medium (40–62.5 mg/kg) or high (80–110 mg/kg) doses did not cause pathomorphological changes in brain neurons and did not cause impaired behavior and activity. In conclusion, REL-1017 did not produce initial or cumulative neurotoxic effects or other evidence of damage to cortical neurons, further encouraging the development of REL-1017 as a potentially safe novel candidate for rapid treatment of MDD.